Studying soil salinity and degradation in Salamiyeh scheme- Syria withintegration of remote sensing (RS) and Geographic information system(GIS) - Mohammed, Sarah (Iraqi Journal of Science, 2024)
The aim of this research study soil salinity and soil degradation with using dataremote sensing (RS) and Geographic information system (GIS), with using program(Arc GIS). The integration of data led to dividing the soil salinity map, and soildegradation. In this research we made group of shape files (geologic, drainage)depending on a group of maps(geologic, topographic), and use ImageTransformational on satellite images taken different times for this study for reach tosalinity soil map by using (Erdas image 9.1)At the end of the research we pointed out the causes of soil degradation andsalinization in the study area.